Strategies in dealing with the Reading Section of ‘TOEFL Prediction’: a case of Aceh EFL Learners - Fera Busfina Zalha; Alfiatunnur Alfiatunnur; Cut Annisa Triana Kamil (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
ABSTRACTHighlighting the TOEFL prediction test, this study attempted to explore EFL learners’ strategies in dealing with the reading comprehension section of the TOEFL prediction test, both in reading the texts and tackling the questions. This study employed a qualitative research design as its approach and a semi-structured interview as the instrument to gain the data. Six participants were purposively selected from the English Language Education Department of UIN Ar-Raniry Banda Aceh. They were interviewed concerning their reading strategies in dealing with the questions in the TOEFL Prediction test. The findings revealed five strategies used by the participants in contending with the TOEFL reading section, classified into reading strategy and test-taking strategy. The reading strategies consist of skimming and scanning the passages, using context to understand the meaning of unfamiliar vocabulary, and utilizing background knowledge. Meanwhile, reviewing the questions and prioritizing easier questions are included in the test-taking strategy. This study proposes further research to investigate the effectiveness of particular strategies in improving EFL students’ performance in facing the reading section.ABSTRAKMengangkat topik tes TOEFL Prediksi, penelitian ini mencoba menyelidiki strategi yang dilakukan oleh mahasiswa-mahasiswi Bahasa Inggris dalam menghadapi bagian Reading Comprehension di tes TOEFL, baik strategi ketika membaca teks maupun ketika menjawab soal-soal yang tersedia. Studi ini menggunakan pendekatan qualitatif dan menggunakan wawancara semi-terstruktur sebagai instrument untuk menghasilkan data. Teknik purposive sampling digunakan dalam memilih enam partisipan untuk studi ini yang keenamnya berasal dari Program Studi Pendidikan Bahasa Inggris UIN Ar-Raniry Banda Aceh. Hasil penelitian ini menunjukkan bahwa ada lima strategi yang digunakan oleh partisipan dalam menyelesaikan TOEFL Reading Section. Kelima strategi tersebut dapat diklasifikasikan kepada reading strategy (strategi membaca) dan test-taking strategy (strategi dalam menghadapi tes). Reading strategies terdiri dari membaca teks dengan menggunakan teknik skimming and scanning, menggunakan konteks untuk dapat memahami makna dari kata-kata yang sukar, dan menggunakan background knowledge (pengetahuan sebelumnya) ketika membaca teks. Sementara mereview pertanyaan dan mengutamakan menjawab pertanyaan-pertanyaan yang lebih mudah termasuk dalam test-taking strategy yang dilakukan oleh partisipan ketika menghadapi tes. Studi ini mendukung penelitian lebih dalam kedepannya terkait keefektifan dari strategi-strategi ini dalam meningkatkan performa mahasiswa-mahasiswi Bahasa Inggris dalam menyelesaikan bagian reading comprehension.